Implementasi Keselamatan dan Kesehatan Kerja (K3) Pada Aktivitas Fabrikasi (Pengelasan, Pemotongan, Penggerindaan) di Kota Medan - ., Rahmatullah; Umroh, Bobby; Amiruddin, Arfis; Siregar, Ahmad Marabdi (Fakultas Teknik UMSU, 2022)
Occupational safety and health (OSH) is basically in the interest of all parties and is a basic right for workers. A safe and comfortable working process is an asset that is maintained continuously for quality and timely production. Work accidents are something that is highly avoided, work accident control must be carried out with methods that are in accordance with the field and industrial conditions. The purpose of the discussion in this paper is, how to control OSH in the fabrication industry in a sustainable manner, how to create good OSH regulations and make the production process safe and comfortable, how to form a good and professional work attitude. Work accidents that occur are actually the end result of a rule and unsafe working conditions. 85% of the causes of accidents are human factors. The fabrication industry carries out several processes such as welding, cutting, final processing and other supporting processes in the workshop. Recommendations have been made and implemented to reduce and control work accidents. The application of OSH in accordance with the concept of occupational health and safety management, theoretically the industry will be able to reduce the number of work accidents even to zero accidents from work accidents.